2017
DOI: 10.1007/s41603-017-0024-3
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Social Behavior: Contributions of Religiosity, Empathic Concern, and Spirituality

Abstract: The aim of the present study is to examine the relationship between empathy, antisocial behavior, religiosity, and spirituality as causal variables of pro-social behavior. The study has also considered the influence of other variables such as age, sex, religious creed, and ethnicity in a Catholic sample of Bolivian university students. A preliminary conceptual model of empathic concern was proposed based on the studied variables. While the relationship between religiosity and pro-social behavior did not prove … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
(53 reference statements)
0
3
0
1
Order By: Relevance
“…Empati ile dindarlık arasındaki pozitif yönlü ilişkiye yönelik başka çalışmalar da mevcuttur (Watson vd., 1985;Francis -Pearson, 1987;Duriez, 2004;Paek, 2006;Damiano vd., 2017;Roth, 2017).…”
Section: şEkil 1: çAlışmanın Aracı Değişken Modeliunclassified
“…Empati ile dindarlık arasındaki pozitif yönlü ilişkiye yönelik başka çalışmalar da mevcuttur (Watson vd., 1985;Francis -Pearson, 1987;Duriez, 2004;Paek, 2006;Damiano vd., 2017;Roth, 2017).…”
Section: şEkil 1: çAlışmanın Aracı Değişken Modeliunclassified
“…Within this literature seminal efforts were made by C. D. Batson to explore the visible connections between religion, altruistic behaviour, and the underlying psychological construct of empathy (see Batson, Schoenrade, & Pych, 1985). Batson and his colleagues argued that the theological account of the relationship between empathy and religion derives from the theory that religion promotes helping behaviour, as exemplified within both the New Testament and the Qur'an, while empathy is understood as fundamental to helping and pro-social behaviour (Rushton, 1980;Batson & Shaw, 1991;Roth, 2017;Silke, Brady, Boylan, & Dolan, 2018).…”
Section: Exploring the Evidencementioning
confidence: 99%
“…A second strand of empirical research within the psychology of religion has involved examining the direct relationship between psychometric measures of empathy and measures of religion or spirituality. Examples of this strand of research are provided by Watson, Hood, Morris, and Hall (1984), Watson, Hood, and Morris (1985), Francis and Pearson (1987), Duriez (2004), Furrow, King, andWhite (2004), Khan, Watson, andHabib (2005), Paek (2006), Francis (2007), Markstrom, Huey, Stilos, andKraus (2010), Francis, Croft, andPyke (2012), Hardy, Walker, Rackham, and Olsen (2012), Huber andMacDonald (2012), Ayten (2013), Glaz (2015), Rashidi, Mousavi, and Esmaeili (2016), Damiano et al (2017), Francis, Lewis, andMcKenna (2017), Roth (2017), Lowicki and Zajenkowska (2017), Ward and King (2018), Stewart, Lawrence, and Burg (2019) and Stewart and Lawrence (2020). Taken together these studies demonstrate that the relationship between religiosity and empathy may vary according to the conceptualisation and operationalisation of religiosity employed and according to the conceptualisation and operationalisation of empathy employed.…”
Section: Exploring the Evidencementioning
confidence: 99%
“…Moreover, religiosity seems to have a significant influence on social behavior and attitudes in various fields ( Donahue and Nielsen, 2005 ). For instance, several studies suggested that religious individuals might be more likely to engage in pro-social behaviors such as volunteering, donating to charity, and helping others ( Roth, 2017 ). However, religious individuals might also tend to hold negative attitudes toward marginalized groups such as LGBTQ+ individuals or those of other faiths ( Westwood, 2022 ).…”
Section: Introductionmentioning
confidence: 99%